Heterogeneous environmental regulation, common prosperity and green innovation - Yuchen Zhang; Jingke Gao (Frontiers in Environmental Science)
Heterogeneous environmental regulation provides dynamic incentives for green innovation through diversity and complementarity, and promotes technological breakthroughs and market responses. Based on the panel data of 30 provinces in China from 2010 to 2020, this paper constructs a bi-directional fixed-effect model to examine the relationship between heterogeneous environmental regulation and green innovation and the moderating effect of common prosperity. The empirical results show that: (1) there is a significant U-shaped relationship between command-control and public participation environmental regulation and green innovation, while there is a significant inverse U-shaped relationship between market incentive environmental regulation and green innovation; (2) Common prosperity has a significant promoting effect on green innovation, and positively regulates the U-shaped relationship between command and control, public participation environmental regulation and green innovation, and negatively regulates the inverted U-shaped relationship between market incentive environmental regulation and green innovation; (3) There are obvious regional differences in the relationship between heterogeneous environmental regulation, common prosperity and green innovation. Therefore, the government should implement differentiated environmental regulation policies, optimize the incentive mechanism for green innovation according to local conditions, build a multi-level environmental governance system, and strengthen the regulatory role of common prosperity to promote the balanced development of green innovation.